2022
DOI: 10.3390/agronomy12071513
|View full text |Cite
|
Sign up to set email alerts
|

Use of SSR Markers for the Exploration of Genetic Diversity and DNA Finger-Printing in Early-Maturing Upland Cotton (Gossypium hirsutum L.) for Future Breeding Program

Abstract: DNA fingerprinting and genetic diversity analysis of 79 early-maturing upland cotton (Gossypium hirsutum L.) cultivars were performed using Simple Sequence Repeat (SSR) molecular markers. Out of 126 pairs of SSR primers, we selected 71 pairs that gave good polymorphisms and clear bands, had good stability, and showed even distribution on the cotton chromosomes, and 142 polymorphic genotypes were amplified. The average number of alleles amplified with the SSR primers was 2.01. The polymorphism information conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…In the present study, the PIC value displayed by each marker varied from a minimum of 0.11 in three primer pairs (CGR-5167, HAU-0590 and SHIN-1400) to a maximum of 0.89 in NAU-5433 (Table 1) which is comparable with Kuang et al (2022) with a range of values of 0.18 to 0.90 based on 71 SSR primers revealing the efficiency of the markers to differentiate the genotypes (Ammad et al 2015;Kencharaddi et al 2018). An average PIC value of 0.59 per SSR locus was noticed indicating the highly informative nature of the markers which correlated with the findings of Ghuge et al (2018), Kuang et al (2022) and Isong et al (2019). Thirty-four markers had a PIC value higher than 0.50 inferring the potential of the markers chosen (Ahmad et al 2015) while the obverse was true for sixteen markers.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…In the present study, the PIC value displayed by each marker varied from a minimum of 0.11 in three primer pairs (CGR-5167, HAU-0590 and SHIN-1400) to a maximum of 0.89 in NAU-5433 (Table 1) which is comparable with Kuang et al (2022) with a range of values of 0.18 to 0.90 based on 71 SSR primers revealing the efficiency of the markers to differentiate the genotypes (Ammad et al 2015;Kencharaddi et al 2018). An average PIC value of 0.59 per SSR locus was noticed indicating the highly informative nature of the markers which correlated with the findings of Ghuge et al (2018), Kuang et al (2022) and Isong et al (2019). Thirty-four markers had a PIC value higher than 0.50 inferring the potential of the markers chosen (Ahmad et al 2015) while the obverse was true for sixteen markers.…”
Section: Resultssupporting
confidence: 71%
“…A total of 186 polymorphic loci were generated as the genotypic data with an average of 3.72 alleles per SSR locus validating the sample size of the study (Table 1) while a higher mean of the alleles shows the diversity or variation present on the chromosomes as the SSR loci are distributed throughout the genome. Earlier, Ali et al (2019) noticed an average of 4.3 alleles per SSR locus while Kuang et al (2022) and Isong et al (2019) noted 142 and 155 alleles with an average of 2.01 and 2.51 alleles per SSR locus, respectively. The number of different alleles (Na) varied from 1 to 7 alleles in marker CGR-6378 (least diverse) and HAU-1430 (most diverse), respectively.…”
Section: Resultsmentioning
confidence: 97%
“…They observed a different number of amplified alleles ranging from 2 to 4 for each locus, with an average of 2.53 alleles per locus. [ 12 , 41 , 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…measured an average PIC value of 0.122 using 287 accessions and 95 SSRs.Tyagi et al (2014) achieved a value of 0.17 with 378 accessions and 120 SSRs Moiana et al (2015). obtained a value of 0.361 from 20 accessions and 27 SSRs, whileQin et al (2015) reported a mean PIC of 0.3 from their study involving 241 accessions and 333 SSRs Kuang et al (2022). obtained PIC of the SSR markers fluctuated from 0.18 to 0.90, with a mean of 0.64 in 79 cotton genotypes.Çelik (2022) found PIC of SSR markers varying from 0.49 to 0.10 with an average PIC value of 0.312 Seyoum et al (2018).…”
mentioning
confidence: 94%
“…Tyagi et al (2014) categorized 381 cotton genotypes into five groups using SSR markers Khan et al (2009). used SSR markers to divide 40 genotypes into three groups, with an average similarity ranging from 36% to 89%.Anderica et al (2018) examined 48 cotton genotypes with 62 SSR markers, resulting in three main clusters Kuang et al (2022). employed SSR markers, grouping all samples into five classes at a similarity coefficient of 0.57.…”
mentioning
confidence: 99%